Association of binge drinking in adolescence and early adulthood with high blood pressure: findings from the National Longitudinal Study of Adolescent to Adult Health (1994–2008). Issue 7 (10th April 2019) - Hayibor, Lisa Ama; Zhang, Jianrong; Duncan, Alexis
Abstract : Background: An investigation of the risk of high blood pressure (HBP) associated with heavy alcohol consumption in adolescence and early adulthood is lacking. Therefore, we aimed to investigate the association between binge drinking from adolescence to early adulthood and the risk of HBP in early adulthood. Methods: We applied logistic regression to publicly available, population-representative data from waves I (1994–1995; ages 12–18) and IV (2007–2008; ages 24–32) of the National Longitudinal Study of Adolescent to Adult Health (n=5114) to determine whether past 12-month binge drinking in adolescence (wave I) and early adulthood (wave IV) was associated with HBP in early adulthood after adjusting for covariates, including smoking and body mass index. HBP was defined according to both the former and new classifications. Results: HBP was significantly, positively associated with infrequent binge drinking (less than once a week) in adolescence based on the new classification (overall: OR 1.23, 95% CI 1.02 to 1.49; male: OR 1.35, 95% CI 1.00 to 1.81) and frequent binge drinking (heavy consumption) in adolescence based on the former classification (overall: OR= 1.64, 95% CI 1.22 to 2.22; male: OR= 1.79, 95% CI 1.23 to 2.60). The risk of HBP was high when participants engaged in frequent binge drinking in both adolescence and early adulthood, especially based on the former classification (overall: OR 2.43, 95% CI 1.13 to 5.20; female: OR 5.81, 95% CI 2.26 to 14.93). Conclusion: Binge drinking in adolescence may increase risk of HBP in early adulthood. This association is independent of other important risk factors for HPB, such as smoking and obesity.